Principal Leadership: Effective Strategy in Increasing Entrepreneurship Spirit in Schools - Arief, Mohammad Yahya; Tsauri, Sofyan; Judijanto, Loso; Ansori; Afra, Nada; Kartiko, Ari (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
Entrepreneurship is one of the five competencies that school principals  must have, entrepreneurship leadership for school principals is very much needed in the era of globalization, school principals are required to be able to provide innovation and creativity to equip students and for the progress of the school. The principal of SMAS Al-Hidayah Dlanggu did the same thing. The principal of SMAS Al-Hidayah Dlanggu is able to instill independence in various schoolowned businesses which are managed directly by students accompanied by the principal and teachers who participate in the school. The businesses owned by SMAS Al-Hidayah Dlanggu include: Jahe Jreng, Koprasi. SMAS Al-Hidayah Dlanggu is one of the schools that is included in the independent school category in east java. The formulation of the problem in this study is how is the principals leadership in increasing entreprenurship and the supporting and inhibiting factors at SMAS Al-Hidayah Dlanggu. The type of research used by researchers is qualitative research with a case study approach. The subjects of this study were school principals, teachers and students. Researchers in collecting data by using data observation, interviews, and documentation. Data analysis using data reduction, data presentation, conclusion drawing. Test the validity of the data using data credibility and confirmability tests. The results of this study indicate that the principals leadership in increasing entrepreneurship at SMAS Al-Hidayah Dlanggu includes the principal having the ability to provide motivation, decision- making ability, communication ability, analytical ability, responsibility and being able to be a good role model. The supporting factors are the enthusiasm and commitment of teachers and students while the inhibiting factors are capital